Preparation of nanocoatings in the presence of precipitated CaCO3 fillers by UV-curing - Izgin, Oner; Aydin, Meral; Arsu, Nergis (ELSEVIER SCIENCE SA, 2013)
Various methods were employed to prepare precipitated calcium carbonate (PCC) particles. Particle size and morphology were dependent on reaction conditions as well as temperature, reagents and stirring, either mechanical or by ultrasound probe sonication. Sonication helped to reduce the size of CaCO3 particles as well as the precipitation time. Sonication was also used to disperse PCC particles in the UV-curable formulations as well as for preparation of the PCC. Formulations containing precipitated calcium carbonates and ground calcium carbonates in various grades were cured by a Mini UV-Cure device. Mechanical and thermal properties of films were characterized with a Dynamic Mechanical Analyzer (DMA). SEM analysis was also used to determine the shape and the size of the PCCs. Sonication decreased the precipitation time of calcium carbonate at least four times more than that of conventional precipitation procedures and the dispersion of particles in the formulations increased to a great extent. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Calcium carbonate; PCC; GCC; UV-curing; Sonication; CALCIUM-CARBONATE; CRYSTALLIZATION; NANOCOMPOSITES; Chemistry; Materials Science